Femvertising and its impact on psychological reactance and purchase intention of Mexican female consumers - Hernández Willoughby, Silvia; Lázaro Pernias, Patricia (Mercados y Negocios, 2023)
This work focuses on the study of the femvertising advertising strategy. It references the feminist theories and the theory of psychological reactance to understand the impact of femvertising on Mexican female consumers' psychological reactance and purchase intention. A mixed methodology was applied, with a content analysis and a reception questionnaire (N=666) to Mexican female consumers. The results show a higher purchase intention and a lower psychological reactance in female consumers to femvertising spots. The main conclusion is that the implementation of the femvertising strategy in advertising spots aimed at Mexican women produces an increase in their purchase intention and a decrease in psychological reactance compared to conventional (non-femvertising) ads because femvertising generates a greater identification of the consumers with the ad by projecting the woman in a more authentic and close way.